2015
DOI: 10.1093/ehjqcco/qcv025
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion therapy for ST-elevation acute myocardial infarction in Eastern Europe: the ISACS-TC registry

Abstract: A substantial number of patients are still not offered any reperfusion therapy in many Eastern European countries with economy in transition, and this was associated with increased 30-day mortality. Time from symptoms onset to admission >12 h was the highest ranking among factors related to lack of reperfusion therapy. Quality improvement efforts should focus on minimizing delay to hospital admission among STEMI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
8

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 21 publications
1
13
0
8
Order By: Relevance
“…is a large observational registry initiated in 2010. The protocol was described previously . Briefly, ISACS‐TC is an investigator‐driven initiative designed to include information on risk factors, clinical presentation, and complications of acute coronary syndromes.…”
Section: Methodsmentioning
confidence: 99%
“…is a large observational registry initiated in 2010. The protocol was described previously . Briefly, ISACS‐TC is an investigator‐driven initiative designed to include information on risk factors, clinical presentation, and complications of acute coronary syndromes.…”
Section: Methodsmentioning
confidence: 99%
“…Beyond the quality of care provided in hospitals, differences in pre-hospital logistics, management and time delays strongly influence patients' outcome. This is particularly true for the Central and Eastern European countries [12,14,15].…”
Section: Commentarymentioning
confidence: 98%
“…To date this international clinical registry has revealed substantial opportunities for healthcare improvement among patients with acute STEMI (as reflected in long times to reperfusion and high 30 day mortality rates), and reported the efficiency of early blockade following acute coronary syndrome (associated with improved left ventricular systolic function and higher in-hospital survival rates) [14,17]. A recent study from the ISACS-TC registry reviewed current practice in antithrombotic therapy and reported that STEMI patients who fail to receive any reperfusion therapy benefit in terms of survival from unfractioned heparin -clopidogrel combination therapy without significant increases in risk of bleeding as compared to combined enoxaparin and clopidogrel therapy [18].…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…Однако, в ряде регионов Восточной Европы и России, в силу вполне понятных причин, такое вмешательство не может быть проведено в приемлемые сроки всем больным ИМпST, и даже большинству из них [3,4]. По-этому в нашей стране на сегодняшний день основным методом восстановления кровотока по инфаркт-свя-занной артерии остается тромболитическая терапия (ТЛТ), которая может быть изолированной, либо со-провождаться последующей рутинной ангиографией, то есть, проводиться в рамках фармакоинвазивного подхода [5].…”
unclassified